IMPROVING OPERATIONAL EFFICIENCY VIA END USER DEVELOPMENT: A WEB-BASED SALES MANAGEMENT SYSTEM FOR DR. BARON POMADE - M. Daud Mursal Lubis; Nurjamiyah (Ninety Media Publisher, 2026)
This study aims to design and implement a Web -based sales management information system for Dr. Baron Pomade using the end user development (eud) method. The background of this research lies in sales processes that were previously conducted manually, which resulted in limited customer reach, slow transaction recording, and the absence of structured sales reports. The main objective is to develop a sales system that enhances operational efficiency, simplifies transaction management, and provides accurate information to support decision-making. The significance of this research is to offer a technological solution that replaces the manual process with an integrated digital system. Furthermore, it encourages active user participation in the system development process through the EUD approach, thereby producing an application that aligns with real operational needs. This study is also expected to serve as a reference for the development of WEB -based information systems in small and medium enterprises, particularly within the men’s cosmetic industry The findings demonstrate that the developed sales information system has been successfully implemented with key features including login, registration, product management, category management, transaction handling, reporting, and configuration settings. System testing confirmed that all features function as intended. The implementation of this system significantly improves business process efficiency, accelerates transaction recording, enhances data accuracy, and supports real-time decision-making. Thus, the study proves that applying the EUD method in sales information system development positively impacts the operational performance of the business. Keywords: Sales Information System, End User Development (Eud), Pomade .